2020
DOI: 10.1101/2020.08.14.250654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERAP2 increases the abundance of a peptide submotif highly selective for the Birdshot Uveitis-associated HLA-A29

Abstract: Birdshot Uveitis (BU) is a blinding inflammatory eye condition that only affects HLA-A29-positive individuals. Genetic association studies linked ERAP2 with BU, an aminopeptidase which trims peptides before their presentation by HLA class I at the cell surface, which suggests that ERAP2-dependent peptide presentation by HLA-A29 drives the pathogenesis of BU. However, it remains poorly understood whether the effects of ERAP2 on the HLA-A29 peptidome are distinct from its effect on other HLA allotypes. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 54 publications
(136 reference statements)
1
16
0
Order By: Relevance
“…(B) The effect of amino acid substitutions for position 62 and 63 on predicted binding affinity for HLA-A29-presented peptides. The average binding scores of 9-mers (n = 948) detected by mass-spectrometry analysis of HLA-A29 reported by Venema et al ( 43 ). Replacement of position 62 and 63 with the most commonly occurring amino acids at that position encoded by HLA-A alleles was done in netMHCpan 4.1 server ( 44 ).…”
Section: The Hla-a29 Protein Structurementioning
confidence: 95%
See 4 more Smart Citations
“…(B) The effect of amino acid substitutions for position 62 and 63 on predicted binding affinity for HLA-A29-presented peptides. The average binding scores of 9-mers (n = 948) detected by mass-spectrometry analysis of HLA-A29 reported by Venema et al ( 43 ). Replacement of position 62 and 63 with the most commonly occurring amino acids at that position encoded by HLA-A alleles was done in netMHCpan 4.1 server ( 44 ).…”
Section: The Hla-a29 Protein Structurementioning
confidence: 95%
“…Other studies from the López de Castro group also demonstrated these ERAP2 effects on the immunopeptidome of risk HLA allotypes of other types of uveitis, such as HLA-B27 ( 94 ). In a recent study, we demonstrated that the effect of ERAP2 on P1 is actually a common feature of ERAP2 observable in the immunopeptidomes of all HLA class I alleles expressed by the cell ( 43 ). Intriguingly, Abelin and coworkers showed that peptides presented by HLA class I allotypes show a depletion for K, R and A residues at P1, which we believe can be attributed to the fact that their studied cell line expresses ERAP2 ( 60 ).…”
Section: Erap1 and Erap2 Shape The Hla-a29 Immunopeptidomementioning
confidence: 96%
See 3 more Smart Citations